Knowledge, attitude and practices of parents regarding their children’s oral health at Edgardo Rebagliati Martins Hospital, in times of COVID-19 pandemic - Sánchez Huamán, Flora Martina (2022)
Background: Oral health is part of a child's overall health and parental involvement in caring for it is essential. Objective: To determine the level of knowledge, attitudes and practices of parents regarding their children’s oral health at Edgardo Rebagliati Martins Hospital, in times of Covid-19 pandemic. Materials and methods: Observational, descriptive, cross-sectional and prospective study, the study sample consisted of 114 parents of children under 14 years of age, a questionnaire was applied that identified the knowledge, attitudes and practices of parents regarding the oral health of their children during the month of April 2022. Results: The most predominant level of knowledge, type of attitudes and level of practices was regular (59.65%), adequate (98.25%) and regular (71.05%) respectively. Most parents didn't know about when to start brushing a child's teeth with fluoride toothpaste (64.91%) and the age of a child with complete primary dentition (64.04%). Conclusions: Most of the parents, despite having had adequate attitudes, presented a regular level of knowledge and practices regarding the oral health of their children in times of Covid-19 pandemic in a reference hospital in Lima, Peru.